Physical meat quality characteristics of Angolan giraffe (Giraffa giraffa angolensis) as affected by sex and muscle - Hoffman, Louwrens C; Silberbauer, Bianca L; Needham, Tersia; Bureš, Daniel; Kotrba, Radim; Strydom, Philip (Meat science, 2022)
Giraffe numbers grow exponentially when farmed, necessitating periodic culling. This study quantified the effect of sex and muscle on the physical quality characteristics of eight giraffe muscles. The Warner-Bratzler shear force (WBSF) was the only parameter to be affected by an interaction between sex and muscle (P < 0.001), although the interaction for the CIE L* values tended towards significance (P = 0.054). Cooking loss (male = 41.6 ± 0.35%; female = 40.7 ± 0.33%; P = 0.024) and CIE L* values (male = 38.8 ± 0.23; female = 37.3 ± 0.27; P = 0.039) were both affected by sex. Muscle had an effect on all physical parameters. The ultimate pH of all muscles was 5.5-5.9; the average WBSF of <43 N for all muscles indicates giraffe meat in this study is tender. This study shows that yield and physical characteristics of giraffe meat are favourable, and the results may be useful for the marketing of giraffe meat.
Keywords: Game meat; Cooking; Colour; žirafy; Giraffes; Cooking loss; Female; zvířata; Drip loss; Meat; vaření; přežvýkavci; pH; kosterní svaly; ženské pohlaví; Male; Muscle, Skeletal; maso; Tenderness; Animals; mužské pohlaví; Ruminants